In Vitro Evaluation of the Primary Stability of Short and Conventional Implants - Pimentel Lopes de Oliveira, Guilherme Jose [UNESP]; Borelli Barros-Filho, Luiz Antonio [UNESP]; Borelli Barros, Luiz Antonio [UNESP]; Queiroz, Thalita Pereira; Marcantonio, Elcio [UNESP] (Allen Press Inc, 2016)
The objective of this study was to evaluate the primary stability of short and conventional dental implants with different platform types at different site densities in vitro. One hundred twenty implants were placed in polyurethane blocks that simulate different bone densities (bone types I and IV). The implants were divided into 10 groups, with 12 implants each according to the type of prosthetic connections (external hexagon, EH; morse taper, MT) and size of the implants (conventional: 4 x 10 mm; short: 5 x 5, 5.5 x 5, 5 x 6, and 5.5 x 6 mm). Insertion torque and resonance frequency analyses were performed to evaluate the primary stability. The Kruskal-Wallis test complemented by Dunn's test and the Mann-Whitney test were used for statistical analysis. These tests were applied at the confidence level of 95% (P<.05). The implants installed in blocks with density type IV exhibited reduced insertion torque compared with implants placed in blocks with density type I. Short implants with EH exhibited increased insertion torque compared with short implants with MT in blocks with bone density type I. In general, implants installed in blocks with density type I exhibited greater primary stability. The short implants with EH with a 5.5-mm diameter and the short implants with MT with a 5-mm diameter exhibited reduced primary stability. No differences between short and conventional implants were noted. Short implants have primary stability and insertion torque at least equivalent to conventional implants irrespective of the platform type and density of the site.
Keywords: bone density; short implants; osseointegration